Maternal experiences of intimate partner violence and C-reactive protein levels in young children in Tanzania. (December 2018) - Slopen, Natalie; Zhang, Jing; Urlacher, Samuel S.; De Silva, Gretchen; Mittal, Mona
Abstract: Intimate partner violence (IPV) is a critical public health issue that impacts women and children across the globe. Prior studies have documented that maternal experiences of IPV are associated with adverse psychological and physical health outcomes in children; however, research on the underlying physiological pathways linking IPV to these conditions is limited. Drawing on data from the 2010 Tanzania Demographic and Health Survey, we examined the relationship between maternal report of IPV in the past 12 months and inflammation among children ages 6 months to 5 years. Our study included 503 children who were randomly selected to provide a blood sample and had a mother who had ever been married and who had completed the Domestic Violence Module, which collected information on physical, sexual, and emotional violence. Analyses were stratified based on a threshold for acute immune activation status, defined by the threshold of CRP > 1.1 mg/L for young children in Tanzania. In bivariate analyses, healthy children whose mothers reported IPV showed a marginally elevated median CRP level compared to children whose mothers did not report IPV (0.35 vs. 0.41 mg/L; p = 0.13). Similarly, among children with active or recent infections, those whose mothers reported IPV had an elevated median CRP compared to children whose mothers did not (4.06 vs 3.09 mg/L; p = 0.03). In adjusted multiple variable regression models to account for child, mother, and household characteristics, maternal IPV was positively associated with (log) CRP in both healthy children and children with active or recent infection. Although longitudinal research with additional biomarkers of inflammation is needed, our results provide support for the hypothesis that inflammation may function as a biological pathway linking maternal IPV to poor psychological and physical health outcomes among children of mothers who are victimized—and this may extend to very young children and children in non-Western contexts.